Pens, swords, and the springs of art : the oral poetry dueling of Palestinian weddings in the Galilee - Yaqub, Nadia G. (Brill studies in Middle Eastern literatures ;, 2007)
Offering an analysis of oral poetry dueling performed at traditional Palestinian weddings, this book addresses poetry dueling as a performative and compositional device, and explores the complex linkages between this tradition and other genres of Arabic poetry.